2018
DOI: 10.1109/led.2018.2794469
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a Planar ${{W}}$ -Band, kW-Level Extended Interaction Oscillator Based on a Pseudospark-Sourced Sheet Electron Beam

Abstract: A W-band extended interaction oscillator (EIO) driven by a pseudospark-sourced sheet electron beam (PS-SEB) is demonstrated in this letter. The idea of combining the advantages of a pseudospark-sourced electron beam (high beam current density), a sheet electron beam geometry (large beam cross-sectional area) and a ladder-like slow wave structure (high gain per unit length) to generate powerful millimeter-wave radiation was experimentally verified. The PS-SEB based EIO produced ~1.2 kW peak output power, an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…With this advanced pseudospark discharge combined with a post-acceleration technique, the experimentally measured pseudospark sheet electron beam achieves a combined beam energy of >30 keV and high beam current in the range of 6A to 21 A, which makes it an excellent sheet electron beam source for planar millimeter wave structures. Two planar sheet beam EIO structures, one in W-band and one in G-band were both simulated and designed to be driven by the pseudospark-sourced sheet electron beam by replacing the collimator in Fig.1 with a planar EIO slow wave structure [10,11]. Initial experimental results demonstrated that an output power of 1.2 kW and 10 W, respectively, was achieved from the W-band and G-band planar EIOs.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…With this advanced pseudospark discharge combined with a post-acceleration technique, the experimentally measured pseudospark sheet electron beam achieves a combined beam energy of >30 keV and high beam current in the range of 6A to 21 A, which makes it an excellent sheet electron beam source for planar millimeter wave structures. Two planar sheet beam EIO structures, one in W-band and one in G-band were both simulated and designed to be driven by the pseudospark-sourced sheet electron beam by replacing the collimator in Fig.1 with a planar EIO slow wave structure [10,11]. Initial experimental results demonstrated that an output power of 1.2 kW and 10 W, respectively, was achieved from the W-band and G-band planar EIOs.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…A machining tolerance with a few microns, a surface roughness with hundreds of nanometers and a small assembling error are typically required in the fabrication of the HFS in a terahertz band SB-TWT. Considerable efforts have been made for the fabrication of the micro-structures in a terahertz vacuum electron device, such as the nano-computer numerical control (CNC) milling techniques [3], [15], [24]- [25], LIGA (German acronym for lithography, electroplating, and molding) process techniques [13], [26], deep-reactive ion etching (DRIE) techniques [26], wire cutting techniques [10], [27], and the 3D-printed mold electroforming [28].…”
Section: Introductionmentioning
confidence: 99%
“…Among various VEDs, the EIO as a linear beam vacuum device has gained considerable attention as a promising millimeter wave oscillator due to its high gain per unit length and compact configuration [8][9][10][11]. At millimeter-wave or THz frequencies, the achievable output power of the conventional O-type VEDs is limited greatly by the electron beam current.…”
Section: Introductionmentioning
confidence: 99%